A compact dual band PIFA antenna for GPS and ISM BAND applications - elkilani samir; Larbi El Abdellaoui; Jamal Zbitou; A. Errkik; Mohamed Latrach (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This work deals with desgin of  a novel  compact  Dual band PIFA Antenna structure. The proposed antenna is validated for GPS and WIFI applications. The antenna is achieved on a lossy FR4 substrate. The final size of the antenna is 100×55×13.235 mm3. The final antenna structure was optimized and validated into simulation, fabrication and test. The proposed multiband PIFA is optimized by using solts technique. The fabricated antenna is validated to cover the operating frequencies of GPS (1.535 -1.7GHz) and BLUTOOTH/WIFI (2.54-2.47GHz) bands.